2016
DOI: 10.1097/iae.0000000000000692
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Optics Imaging of Foveal Sparing in Geographic Atrophy Secondary to Age-Related Macular Degeneration

Abstract: Adaptive optics allows the appreciation of differences in reflectivity between regions of GA and foveal sparing. Preservation of functional cone photoreceptors was demonstrated on en face AO IR images in areas of foveal sparing detected by confocal scanning laser ophthalmoscope near-IR autofluorescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…This may be because the preserved foveal region was too small to evoke normal ERGs, and we suggest that the etiology of our three cases was similar to that reported by Kondo et al 44 A sparing of the fovea is commonly observed in different types of macular diseases, such as in ABCA4-and PRPH2associated retinopathies, 17,18,43,[45][46][47][48] mitochondrial retinal dystrophy, 49 macular dystrophy with CRB1 mutation, 50 and agerelated macular degeneration. [51][52][53][54] The explanations for the physiologic and anatomic sparing of the fovea have been presented in many publications. [55][56][57][58][59][60][61][62][63] However, foveal sparing in these macular diseases is usually accompanied by RPE atrophy around the fovea, and the border between the atrophic region and normal fovea is distinct.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be because the preserved foveal region was too small to evoke normal ERGs, and we suggest that the etiology of our three cases was similar to that reported by Kondo et al 44 A sparing of the fovea is commonly observed in different types of macular diseases, such as in ABCA4-and PRPH2associated retinopathies, 17,18,43,[45][46][47][48] mitochondrial retinal dystrophy, 49 macular dystrophy with CRB1 mutation, 50 and agerelated macular degeneration. [51][52][53][54] The explanations for the physiologic and anatomic sparing of the fovea have been presented in many publications. [55][56][57][58][59][60][61][62][63] However, foveal sparing in these macular diseases is usually accompanied by RPE atrophy around the fovea, and the border between the atrophic region and normal fovea is distinct.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the pathologic mechanism for the foveal sparing may differ between the cases with POC1B mutations and other macular dystrophies. 17,18,43,[45][46][47][48][49][50][51][52][53][54] Although the numbers of the eyes with foveal sparing are limited, further investigations to determine whether there is a significant association between the genotype and RPE findings (i.e., the presence or absence of RPE atrophy) in a large cohort with foveal sparing could determine the mechanism of the foveal sparing.…”
Section: Discussionmentioning
confidence: 99%
“…Cells are variably identified among these authors, including RPE 48 , RPE packed with pigment granules 4, 6, 54, 55 , RPE/macrophages 38 , and melanin-containing cells. 59 Like others using electron microscopy, we considered these subretinal cells RPE, because they contained numerous RPE-characteristic granules at a concentration resembling that of cells in the RPE layer 8, 18 and because evidence for other cell types was lacking.…”
Section: Discussionmentioning
confidence: 99%
“…32,37 Such pattern of early relative preservation of visual acuity and then rapid loss is reminiscent of numerous maculopathies that show preservation of visual acuity despite severe central retinal disease. [79][80][81][82][83][84] Thus, visual acuity in this condition, as in most IRDs, is not a reliable indicator of the severity of the central retinal phenotype, although it is critical to the patients' quality of life. 27,78 Once the central island is compromised a rapid decline of the patients' VA may be expected.…”
Section: Discussionmentioning
confidence: 99%